Made in Britain : nation and emigration in nineteenth-century America - Tuffnell, Stephen, 1987- (University of California Press, 2020)
"The United States was made in Britain. For over a hundred years following independence, a diverse and lively crowd of emigrant Americans left the United States for Britain. From Liverpool and London, they produced Atlantic capitalism and managed transfers of goods, culture, and capital that were integral to U.S. nation-building. In British social clubs, emigrants forged relationships with elite Britons that were essential not only to tranquil transatlantic connections, but also to fighting southern slavery. As the United States descended into Civil War, emigrant Americans decisively shaped the Atlantic-wide battle for public opinion. Equally revered as informal ambassadors and feared as anti-republican contagions, these emigrants raised troubling questions about the relationship between nationhood, nationality, and foreign connection. Blending the histories of foreign relations, capitalism, nation-formation, and transnational connection, Stephen Tuffnell compellingly demonstrates that the United States' struggle toward independent nationhood was entangled at every step with the world's most powerful empire. With deep research and vivid detail, Made in Britain uncovers this hidden story and presents a bold new perspective on the nineteenth-century cross-Atlantic relations"--